2021
DOI: 10.3389/fimmu.2021.609543
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Porcine RIG-I Like Receptors Revealed the Positive Regulation of RIG-I and MDA5 by LGP2

Abstract: The RLRs play critical roles in sensing and fighting viral infections especially RNA virus infections. Despite the extensive studies on RLRs in humans and mice, there is a lack of systemic investigation of livestock animal RLRs. In this study, we characterized the porcine RLR members RIG-I, MDA5 and LGP2. Compared with their human counterparts, porcine RIG-I and MDA5 exhibited similar signaling activity to distinct dsRNA and viruses, via similar and cooperative recognitions. Porcine LGP2, without signaling act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 63 publications
0
9
0
Order By: Relevance
“…Less is known about the role of LGP2 in filovirus infection. Recent data have shown that LGP2 may play a role in regulating RIG-I and MDA5 [68,[95][96][97][98], but it is unknown whether filovirus infection may influence this regulation.…”
Section: Rig-i-like Receptors and Ifn Signalingmentioning
confidence: 99%
“…Less is known about the role of LGP2 in filovirus infection. Recent data have shown that LGP2 may play a role in regulating RIG-I and MDA5 [68,[95][96][97][98], but it is unknown whether filovirus infection may influence this regulation.…”
Section: Rig-i-like Receptors and Ifn Signalingmentioning
confidence: 99%
“…As shown in Table 1 , our results showed that the expression of TLR2, TLR3, TLR4 and TLR8 were markedly up-regulated and the expression of other RNA sensors (DHX9, DHX15, DHX29, DHX36, DHX58, ZNFX-1, DDX1, DDX3X and DDX6) were significantly down-regulated in the PAMs with a PRRSV-ADE infection. Multiple studies reported that these viral RNA sensors could also specifically sense pathogenic RNA to stimulate the TIR-domain-containing adapter-inducing interferon-β (TRIF)- or the mitochondrial antiviral signaling protein (MAVS)-mediated type I IFN signaling, the type III IFN signaling and the pro-inflammatory cytokines signaling, except for the TLRs [ 14 , 15 , 16 , 17 , 18 ]. Furthermore, we also found that COX-5B was significantly up-regulated, while TRIM25, TRIM21, TRIM27 and TRIM26 were significantly down-regulated in the PAMs with a PRRSV-ADE infection in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Although LGP2 itself is inactive in signaling, it has a stronger ability to bind with dsRNA and enables to regulate RIG-I and MDA5 activity [ 8 ]. In spite of the controversial role of LGP2 in the regulation of RIG-I and MDA5 signaling [ 5 , 9 , 10 , 11 ], our recent work showed that porcine LGP2 is able to positively regulate RIG-I and MDA5 signaling by promoting dsRNA binding and exerts an antiviral role against several porcine viruses [ 12 ].…”
Section: Introductionmentioning
confidence: 99%